Simulation of the crosswind and the steam addition effect on the flare flame - . WUSNAH; . YUNARDI; NOVI SYLVIA; . ELWINA; YAZID BINDAR (Syiah Kuala University, 2014)
This paper presents the results obtained from the application of computational fluid dynamics (CFD) to modelling the crosswind and steam addition effect on a turbulent non-premixed flame. A pre-processor software GAMBIT was employed to set up the configuration, discretisation, and boundary conditions of the flame being investigated. The commercial software Fluent 6.3 was used to perform the calculations of flow and mixing fields as well as combustion. Standard k-ε and eddy dissipation models were selected as solvers for the representation of the turbulence and combustion, respectively. The results of all calculations are presented in the forms of contour profiles. During the investigation, the treatment was performed by setting a velocity of fuel at 20 m/s with varied cross-wind velocity at 3.77 m/s, 7.5 m/s and 10 m/s, and steam/fuel ratio at 0.14, 0.25 and 2.35. The results of the investigation showed that the standard k-ε turbulence model in conjunction with Eddy Dissipation Model representing the combustion was capable of producing reliable phenomena of the flow field and reactive scalars field in the turbulent non-premixed flame being investigated. Other results of the investigation showed that increasing the velocity of the crosswind, when the fuel velocity was kept constant, significantly affected the flow field, temperature and species concentrations in the flare flame. On the other hand, when the velocity of the fuel was varied at the constant crosswind velocity, the increasing velocity of the fuel gave positive impact as it enabled to counteract the effect of crosswind on the flare flame. The velocity of the crosswind very influence of combustion efficiency, from result of the investigation showed that increasing the velocity of the crosswind significantly affected the combustion efficiency, other result of the inverstigation showed that steam addition will very influencing combustion, excelsior the steam/fuel ratio results the combustion efficiency decrease